Rancang Bangun Media Pembelajaran Interaktif Menggunakan Adobe Flash CS6 Berbantuan Circuit Verse pada Elemen Penerapan Rangkaian Elektronika - Nurul Hidayah; Yasdinul Huda; Ilmiyati Rahmi Jasril; Hendra Hidayat (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to develop interactive learning media for logic gate material in Industrial Electronics Engineering subjects at SMK Negeri 5 Batam by utilizing Adobe Flash CS6 integrated with CircuitVerse. This media is designed to provide a more interesting, interactive, and applicable learning experience, so it is expected to improve students' understanding of the concept of logic gates which is a basic material in the field of electronics. The study uses a Research and Development (R&D) approach with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Research data were collected through validation by material experts and media experts, as well as practicality tests involving students. Data collection instruments were in the form of validation sheets and student response questionnaires. The validation results showed that the developed learning media obtained a score of 88.20% from material experts and 93.88% from media experts, both of which are in the